Experimenting and evaluating the impact of DoS attacks on different SDN controllers - Alashhab, A.A. (Institute of Electrical and Electronics Engineers Inc., 2021)
The flexibility and centrality of Software Defined Networking (SDN) has made it vulnerable to Denial of Service (DoS) attacks. Despite of the advantages, the potential DoS attacks may compromise the functions of switches, control channel and SDN controller. This paper is devoted to simulating and analyzing the impact of DoS packet in flooding attacks on SDN controller and control channel which may even affect the whole SDN network. The network performance is tested and emulated by using different testing tools of simulation in Mininet such as Hping3 and Wireshark. Likewise, the three different SDN controllers Floodlight, Ryu and POX performed as the uplink control data. Our findings show that with quite limited resources in pure open source SDN controllers, an attacker can produce a major distraction against an SDN networks. The recovery rate of SDN controllers show variable delay weakness between controllers' performance: that the best result for the Ryu controller after sequences packets 6, and the worst recovery rate for POX controller after sequences packets 47. Â© 2021 IEEE.